Components influencing craving in substance use disorders - Baley, John Winters (2014)
Previous research has established craving as a significant element in models of Substance Use Disorders (SUD). Craving is a new criterion for SUD in the most recent Diagnostic and Statistical Manual of Mental Illness (DSM-5) and is also considered a predictor of relapse post-treatment. Moreover, research indicates that stress, negative emotional states, and symptoms of Posttraumatic Stress Disorder (PTSD) can influence craving, suggesting that affective states are key to the treatment and relapse risk of individuals with SUD. In fact, recent research suggests that these affective elements may share a common core which influences craving and subsequent relapse. This study introduces a new measure which attempts to isolate that common core, and aims to explore the interplay among stress, negative emotionality, PTSD symptoms, and craving in a clinical sample comprised of adults with SUDs. Findings may aid in conceptualization and treatment (including relapse prevention) for this population.